Pluralisme Agama dan Toleransi dalam Islam Perspektif Yusuf Al-Qaradhawi - Sukron Ma’mun (Bina Nusantara University, 2013)
Religious pluralism is a phenomenon that cannot be avoided. If religious pluralism is not rightly understood by religious believers, pluralism will lead to interreligious conflict. This paper would like to reveal the thoughts of Yusuf al-Qaradawi about religious pluralism and tolerance in Islam. The purposes of writing this paper are exploring the concept of religious pluralism and tolerance, describing the biography of Yusuf al-Qaradawi and his influences in Islamic studies, and describing the thoughts of Yusuf al-Qaradawi about religious pluralism and tolerance in Islam. In paper the author uses descriptive-analytical method. The procedures are data collection, classification of data, data analysis, and drawing conclusions. Source of the data was gained from information available in the literatures. The data analysis was done by using content analysis method (content analysis), which is an attempt to explore the symbolic meaning of the message or the contents of a book or other writings products. Result showed that pluralism in Islam is based on the fact that God has created man in the diversity and plurality. For that to avoid disaster or human conflict, it is necessary tolerance values. Qur'an, Sunnah, and behavior as scholars have become reasons to appreciate the difference.